PENGARUH PELAKSANAAN PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PERUMAHAN PT RAFINDO MUTIARA ABADI (KASUS HUNIAN PERUMAHAN MUTIARA TENAYAN RAYA PEKANBARU) - Raka, Muhammad; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aim to determine how much influence promotion implementation and product quality have on consumer purchasing decisions. The sample in this study was taken as many as 57 respondents who were determined using Slovin formula. Data collection techniques in this study using interview methods and questionnaires filled by consumen who bought house at Mutiara Tenayan Raya Pekanbaru Housing. Data obtained using simple regression analysis and multiple regression analysis. The result of this study indicate that promotion implementation has a significant effect on consumer purchasing decisions. Product quality has a significant effect on consumer purchasing decisions. And simultaneously promotion implementation and product quality have a significant effect on consumer puchasing decisions. Kata kunci : Promotion Implementation, Product Quality, Consumer Purchasing Decisions